Training on Solar Cell Utilization for Edutourism Enhancement - Rifky; Heriyani, Oktarina; Mugisidi, Dan; Ariyansah, Riyan; Fauzi, Herman (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study article seeks to examine the efficacy of a training program centered on solar cell application to improve edutourism in Pulau Pari. The study seeks to tackle the issue of insufficient knowledge and skills in renewable energy within the local community and emphasize the importance of integrating sustainable practices in the tourism industry. Method: This investigation implements a mixed-methods approach. Quantitative data was gathered using pre- and post-training evaluations to assess the enhancement of participants' knowledge and skills. Qualitative data was acquired via interviews and observations to elucidate the individuals' experiences and perceptions. The data underwent analysis by descriptive statistics and thematic analysis. Practical Applications: The results of this study have practical implications for the tourism industry as a whole and for the local community of Pulau Pari. The outputs of the training program can guide the creation of analogous programs in other locations, fostering the implementation of renewable energy and sustainable practices in edutourism. The findings may also assist policymakers and tourist stakeholders in incorporating solar cell implementation into their strategy for sustainable tourism development. Conclusion: The study's results demonstrate that the training program on solar cell application for enhancing edutourism in Pari Island has successfully improved participants' knowledge and abilities in renewable energy. The program can enhance the island's sustainable development by diminishing reliance on traditional energy sources and fostering eco-friendly tourism habits. The findings highlight the importance of integrating renewable energy education and training into community-based tourism programs to promote sustainability and resilience against global environmental concerns.